Economic development and poverty in modern times of crisis (Journal of Economic Research & Business Administration, 2016)
Economic development in the conditions of crisis it is possible only in close interrelation with economic growth taking into account division of the income. A negative factor is the sharp increase in distinction between intensive enrichment influential and prompt deterioration of a state poor. Therefore, consideration of a problem of poverty in the state, influences of level of poverty on growth of GNP, identification of level of poverty is very important, consideration of values of minimum wage and a living wage is very important. One of factors characterizing economy of Kazakhstan in the conditions of diversification of economy is the standard of living socially of lower-income strata. Indicators of the comparative analysis of a condition of poverty in Kazakhstan revealed unexpected contradictory questions which can influence economic development. In conclusion, particularly economic and social development of Kazakhstan for 2014 is characterized by that in-depth classification of per capita income corresponds to a market economy. Also present a proposal, taking into account that in emergency situations some measure of life of the population is not prepared for them.
Keywords: market economy; GNP (gross national product); poverty; the absolute approach; the relative approach; productive resources.